A 2021 Horizon Scan of Emerging Global Biological Conservation Issues. (January 2021) - Sutherland, William J.; Atkinson, Philip W.; Broad, Steven; Brown, Sam; Clout, Mick; Dias, Maria P.; Dicks, Lynn V.; Doran, Helen; Fleishman, Erica; Garratt, Elizabeth L.; Gaston, Kevin J.; Hughes, Alice C.; et al.
Abstract : We present the results from our 12th annual horizon scan of issues likely to impact biological conservation in the future. From a list of 97 topics, our global panel of 25 scientists and practitioners identified the top 15 issues that we believe society may urgently need to address. These issues are either novel in the biological conservation sector or represent a substantial positive or negative step-change in impact at global or regional level. Six issues, such as coral reef deoxygenation and changes in polar coastal productivity, affect marine or coastal ecosystems and seven relate to human and ecosystem-level responses to climate change. Identification of potential forthcoming issues for biological conservation may enable increased preparedness by researchers, practitioners, and decision-makers. Highlights: Our 12th annual horizon scan identified 15 emerging issues of concern for global biodiversity conservation. A panel of 25 scientists and practitioners submitted a total of 97 topics that were ranked using a Delphi-style technique according to novelty and likelihood of impact on biodiversity conservation. The top 38 issues were discussed at an online meeting held in September 2020 during which issues were ranked according to the same criteria. Six of the 15 issues primarily affect marine or coastal ecosystems and seven are related to human and ecosystem-level responses to anthropogenic climate change. Other emerging issues include complete coverage of Indian states for sustainable farming and the potential for use of self-healing building materials.